Slime for dinner - Stilton, Geronimo; Stilton, Geronimo; Angleberger, Tom; Dami, Elisabetta; Barba, Corey; Kemper, Kristin; Clement, Emily (Translator) (New York, NY : Graphix, an imprint of Scholastic, 2021)
"Geronimo, Thea, and Trap were invited to a spine-tingling mystery dinner at Cacklefur Castle! There they find spiders, bats, and ... something slimy! Can Geronimo solve teh mystery before he is frightened out of his fur?"-- Back cover.
"Based on Cena con mistero (original title) copyright 2018 by Mondadori Libri S.pA for Piemme Italia."--Title page verso.
Geronimo Stilton is a book character who is the attributed author.
Translated from the Italian.
Keywords: Stilton, Geronimo -- Comic books, strips, etc. -- Juvenile fiction; Stilton, Geronimo -- Fiction; Mice -- Comic books, strips, etc. -- Juvenile fiction; Dinners and dining -- Comic books, strips, etc. -- Juvenile fiction; Castles -- Comic books, strips, etc. -- Juvenile fiction; Journalists -- Comic books, strips, etc. -- Juvenile fiction; Private investigators -- Comic books, strips, etc. -- Juvenile fiction; Haunted houses -- Comic books, strips, etc. -- Juvenile fiction; Comic books, strips, etc. -- Italy -- Translations into English; Graphic novels -- Italy -- Translations into English; Mice -- Fiction; Dinners and dining -- Fiction; Castles -- Fiction; Journalists -- Fiction; Private investigators -- Fiction; Haunted houses -- Fiction; Comics (Graphic works); Graphic novels; Detective and mystery comics; Horror comics